Expectations of and for Clerkship Directors 2.0: A Collaborative Statement from the Alliance for Clinical Education. Issue 4 (8th August 2021) - Morgenstern, Bruce Z.; Roman, Brenda J. B.; DeWaay, Deborah; Golden, W. Christopher; Malloy, Erin; Reddy, Rishindra M.; Rutter, Ann E.; Salas, Rachel; Soni, Madhu; Starr, Stephanie; Sutton, Jill; Wald, David A.; et al.
Abstract: This article presents an update of the collaborative statement on clerkship directors (CDs), first published in 2003, from the national undergraduate medical education organizations that comprise the Alliance for Clinical Education (ACE). The clerkship director remains an essential leader in the education of medical students on core clinical rotations, and the role of the CD has and continues to evolve. The selection of a CD should be an explicit contract between the CD, their department, and the medical school, with each party fulfilling their obligations to ensure the success of the students, the clerkship and of the CD. Educational innovations and accreditation requirements have evolved in the last two decades and therefore this article updates the 2003 standards for what is expected of a CD and provides guidelines for the resources and support to be provided. In their roles as CDs, medical student educators engage in several critical activities: administration, education/teaching, coaching, advising, and mentoring, faculty development, compliance with accreditation standards, and scholarly activity. This article describes (a) the work products that are the primary responsibility of the CD; (b) the qualifications for the CD; (c) the support structure, resources, and personnel that are necessary for the CD to accomplish their responsibilities; (d) incentives and career development for the CD; and (e) the dedicated time that should be provided for the clerkship and the CD to succeed. Given all that should rightfully be expected of a CD, a minimum of 50% of a full-time equivalent is recognized as appropriate. The complexity and needs of the clerkship now require that at least one full-time clerkship administrator (CA) be a part of the CD's team. To better reflect the current circumstances, ACE has updated its recommendations for institutions and departments to have clear standards for what is expected of the director of a clinical clerkship and have correspondingly clear guidelines as to what should be expected for CDs in the support they are provided. This work has been endorsed by each of the eight ACE member organizations.